2010
DOI: 10.1128/aem.00478-10
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Biodiversity in Sulfide Structures of Active and Inactive Vents at Deep-Sea Hydrothermal Fields of the Southern Mariana Trough

Abstract: The abundance, diversity, activity, and composition of microbial communities in sulfide structures both of active and inactive vents were investigated by culture-independent methods. These sulfide structures were collected at four hydrothermal fields, both on-and off-axis of the back-arc spreading center of the Southern Mariana Trough. The microbial abundance and activity in the samples were determined by analyzing total organic content, enzymatic activity, and copy number of the 16S rRNA gene. To assess the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(149 citation statements)
references
References 83 publications
(107 reference statements)
11
138
0
Order By: Relevance
“…22), as their energy sources, even if the supply of hydrothermal fluids ceases. The difference between active and inactive chimney samples may reflect the temporal change before and after the cease of hydrothermal activity, i.e., temperature, pH and Eh, in addition to availability of Table 24.1 for the sample description reduced chemical species (Kato et al 2010), which is consistent with the previous study of 9 N EPR (Sylvan et al 2012).…”
Section: Comparison Of Community Structuressupporting
confidence: 79%
See 2 more Smart Citations
“…22), as their energy sources, even if the supply of hydrothermal fluids ceases. The difference between active and inactive chimney samples may reflect the temporal change before and after the cease of hydrothermal activity, i.e., temperature, pH and Eh, in addition to availability of Table 24.1 for the sample description reduced chemical species (Kato et al 2010), which is consistent with the previous study of 9 N EPR (Sylvan et al 2012).…”
Section: Comparison Of Community Structuressupporting
confidence: 79%
“…The 16S rRNA gene sequences were recovered from ironrich mats (YS16 and YS18) (Kato et al 2009a), active (AFhm, APcsc, APbsc, AAcs) and inactive chimneys (IPltc, IYdc, Inoc) (Kato et al 2010;Kato et al Chap. 9), crustal fluids obtained from boreholes (Fapm1a, Fapm1b, Papm3, F2apm1), a natural vent fluid (Fnv) and ambient seawater (Pasw and Fasw) (Kato et al 2009b) in the SMT hydrothermal fields, i.e., Snail, Pika, Archaean, Kaiko and Yamanaka sites (Suppl.…”
Section: Re-analysis Of 16s Rrna Gene Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recently, massive sulfide deposits and Mn crusts on the deep seafloor have been focused on as mineral www.intechopen.com resources (Rona, 2003;Hoagland et al, 2010). There are diverse microbes on/in these seafloor minerals (Kato et al, 2010;Nitahara et al, 2011). Microbial biogeography on the deep seafloor will contribute ultimately to develop deep-sea mining techniques utilizing microbes in future.…”
Section: Seafloor Microbial Communitiesmentioning
confidence: 99%
“…To assess how the environmental similarity (i.e., contemporary physicochemical condition) and geographic distance (i.e., historical event) affect on the distribution patterns of biodiversity of microbial communities or population, -diversity are associated with physicochemical and geographic differences among each environment. A variety of habitats in natural environments have been targeted for microbial biogeography, such as soil (Cho & Tiedje, 2000;Fierer & Jackson, 2006), lake sediments (Yannarell & Triplett, 2005), ocean (GarcĂ­a-MartĂ­nez & RodrĂ­guez-Valera, 2000), deep-sea sediments (Schauer et al, 2009) and deep-sea hydrothermal fields (Kato et al, 2010). These studies have suggested that the distribution pattern of microbes in habitats is controlled by not only environmental factors (e.g., pH, salinity and oxygen concentration) but also geographic isolation.…”
mentioning
confidence: 99%